2015
DOI: 10.1042/bj20140881
|View full text |Cite
|
Sign up to set email alerts
|

Steatosis inhibits liver cell store-operated Ca2+ entry and reduces ER Ca2+ through a protein kinase C-dependent mechanism

Abstract: Lipid accumulation in hepatocytes can lead to non-alcoholic fatty liver disease (NAFLD), which can progress to non-alcoholic steatohepatitis (NASH) and Type 2 diabetes (T2D). Hormone-initiated release of Ca²⁺ from the endoplasmic reticulum (ER) stores and subsequent replenishment of these stores by Ca²⁺ entry through SOCs (store-operated Ca²⁺ channels; SOCE) plays a critical role in the regulation of liver metabolism. ER Ca²⁺ homoeostasis is known to be altered in steatotic hepatocytes. Whether store-operated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 50 publications
3
57
0
Order By: Relevance
“…The interaction of PKC and store‐operated Ca 2+ entry has been reported. Steatosis was shown to inhibit liver cell store‐operated Ca 2+ entry and reduce the endoplasmic reticulum Ca 2+ content through a PKC‐dependent mechanism . The results show that diosgenin‐evoked [Ca 2+ ] i increases were inhibited by enhancing or inhibiting PKC activity by 30%.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of PKC and store‐operated Ca 2+ entry has been reported. Steatosis was shown to inhibit liver cell store‐operated Ca 2+ entry and reduce the endoplasmic reticulum Ca 2+ content through a PKC‐dependent mechanism . The results show that diosgenin‐evoked [Ca 2+ ] i increases were inhibited by enhancing or inhibiting PKC activity by 30%.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of steatosis is often with palmitate or a drug such as amiodarone, followed in various studies performed to understand the mechanism and/or to test potential therapeutics . Amiodarone (Scheme ), a commonly used antiarrhythmic drug, is one of the compounds used to induce steatosis in HepG2 cells . In order to study intracellular lipid droplets, various fluorescent probes have been developed for imaging .…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that amiodarone directly inhibits fatty acid oxidation enzymes and results in intracellular lipid accumulation. Amiodarone is used to induce lipid accumulation in cells . We first evaluated the cytotoxicity of amiodarone on HepG2 cells since there is evidence suggesting amiodarone may have significant cytotoxicity on HepG2 cells .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PKC is a multimember protein kinase family involved in regulating functions of many other proteins through phosphorylating the hydroxyl groups on serine and threonine amino acid residues. PKC itself can be activated by signalling molecules, such as increased concentrations of diacylglycerol or calcium ions (Ca 2þ ) [25]. PKC enzymes are known to play important roles in several signal transduction cascades [26].…”
Section: Introductionmentioning
confidence: 99%